2013
DOI: 10.3758/s13414-013-0512-3
|View full text |Cite
|
Sign up to set email alerts
|

Salient stimuli capture attention and action

Abstract: Reaction times in a visual search task increase when an irrelevant but salient stimulus is presented. Recently, the hypothesis that the increase in reaction times was due to attentional capture by the salient distractor has been disputed. We devised a task in which a search display was shown after observers had initiated a reaching movement toward a touch screen. In a display of vertical bars, observers had to touch the oblique target while ignoring a salient color singleton. Because the hand was moving when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 63 publications
3
21
1
Order By: Relevance
“…1B; see supplemental methods), we found significant deviation that appeared immediately and persisted through 88% of the movement trajectory (Fig 1C; see methods for details on statistical calculation). This finding is consistent with previous reach movement studies suggesting that action is automatically directed towards physically salient objects [1315]. The initial trajectory angle (ITA) [17] of hand movements was also greater on distractor present trials (18.7°) than absent trials (15.5°), t (15)= 5.99, p < 001 (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1B; see supplemental methods), we found significant deviation that appeared immediately and persisted through 88% of the movement trajectory (Fig 1C; see methods for details on statistical calculation). This finding is consistent with previous reach movement studies suggesting that action is automatically directed towards physically salient objects [1315]. The initial trajectory angle (ITA) [17] of hand movements was also greater on distractor present trials (18.7°) than absent trials (15.5°), t (15)= 5.99, p < 001 (Fig.…”
Section: Resultssupporting
confidence: 91%
“…For example, one possibility is that differences in the timing of response execution between the two tasks contributed to the divergent results. Nevertheless, the present results provide clear evidence of reduced interference from highly salient distractors during goal-directed action, which are at odds with prevailing views of the impact of salience on performance [78] and add to a growing number of studies highlighting dissociations in selection for vision and selection for action [13,1617]. …”
Section: Discussioncontrasting
confidence: 92%
“…A number of previous studies have found that goal-directed action is automatically biased towards perceptually salient feature singleton objects (e.g., Kerzel & Schönhammer, 2013; Wood et al, 2011). The present results build on these findings to show that looming motion can also bias reach movement trajectories automatically.…”
Section: Discussionmentioning
confidence: 99%
“…2C), p < .001, indicating that the hand was consistently pulled in the direction of looming distractors. Furthermore, this result is not because observers were simply delaying target selection by moving their hand towards the center of all items when a distractor was present 2 (e.g., Kerzel & Schönhammer, 2013). If that were the case, reach movements would be unaffected by the specific looming distractor location.…”
Section: Experiments 1a: Looming Motion and Goal-directed Actionmentioning
confidence: 94%
See 1 more Smart Citation